Rancang Bangun Website Pembelajaran Interaktif Berbasis Dokumen PDF Menggunakan Artificial Intelligence - Suharyanti; Permadi, Raihan Ananda (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2025)
The use of websites as digital learning media continues to grow; however, conventional PDF-based learningstill lacks interactivity and ef icient content understanding. This study aims to design and develop a PDF-basedlearning website integrated with Artificial Intelligence (AI). The research method includes system design usingUnified Modeling Language (UML), web application development with the Flask framework, and MySQL as thedatabase. The developed system provides PDF upload, automatic content summarization, quiz generation, andAI-based question-and-answer features. The results show that the system improves learning ef iciency andsupports better comprehension of learning materials. This website is expected to support more interactive andef ective digital learning environments.